Statistics in research: basic concepts and techniques for research workers - Ostle, Bernard; Mensing, Richard W. (Iowa: Iowa State University Press/ AMES, 1975)
The role of statistics in research. Probability. Elements of sampling and descriptive statistics. Sampling distributions. Statistical inference: estimation. Statistical inference: testing hypotheses. Regression analysis. Correlation analysis. Design of experimental investigations. Completely randomized design. Randomized complete block design. Additional designs and techniques related to experimental designs. Analysis of covariance. Distribution-free methods. Topics in statistical quality control and reliability.
The Role of statistics In Research -- Probability -- Elements of Sampling and Descriptive Statistics -- Sampling Distributions -- Statistical Inference: Estimation -- Statistical Inference: Testing Hypotheses -- Regression analysis -- Correlation Analysis -- Design of Experimental Investigations -- completely Randomized Design -- Randomized Complete Block Design -- Additional Designs and Techniques Related to Experimental Designs -- Analysis of Covariance -- Distribution- Free Methods -- Topics in Statistical Quality control and Reliability
Includes index
Keywords: Statistics; Statistics theory and methods; Research; Probability & Statistics